Study on Crystallization Mechanism of Asphalt Mixture in Bridge Deck Pavement - Chuanxi Luo; Duanyi Wang; Jian Li; Jun He (Buildings, 2023)
This study focuses on unknown crystal precipitates from an asphalt mixture used in bridge deck pavement layers. X-ray fluorescence spectroscopy was used to analyze the composition and source of crystals in the asphalt mixture used in bridge deck pavement, and infiltration tests, porosity tests, splitting tests and multi-wheel rutting tests were carried out to determine the precipitation area and non-precipitation area to explain the influence of crystals on the road performance of an asphalt pavement. A nuclear-free densitometer and 3D ground-penetrating radar (3D GPR) were used to detect the porosity and thickness uniformity of the whole section to study the formation mechanism of crystals. The results showed that the main components of crystals were water molecules, while the rest mainly came from machine-made sand, and there was no significant difference in pavement performance in the areas where crystals precipitated. The crystals were mainly caused by rainwater penetrating into the pavement through coarse segregation areas and collecting in the depression of the lower bearing layer. Under high temperature, the solution precipitated out of the pavement and formed crystals.